An unusual pathogen in a case of community acquired pneumonia - Agarwal, Isha; Dutta, Adwitiya; Das, Uddalak; Jana, Pulak Kumar (The ESRF Research Journal for Undergraduate Medical Students, 2023)
Staphylococcus epidermidis, so far thought of primarily as a harmless commensal bacteria on human skin, is now recognizedas a significant opportunistic pathogen. It generally causes nosocomial infections at a rate that is comparable to that of its relative, the more virulent Staphylococcus aureus. Even though S. epidermidis infections seldom result in life-threatening illnesses, the frequency and difficulty of treating them place a significant strain on the public health system. Our casedescribes the case of a healthy adolescent with no known risk factors who developed S.epidermidis pneumonia and was subsequently managed with antibiotics to full recovery